Flood Insurance in New York City Following Hurricane Sandy - Dixon, Lloyd (RAND Corporation, 2013)
Flood insurance payments can help households and businesses recover from an event and get the economy moving again. Premiums can also provide appropriate incentives to avoid or mitigate risk. This report examines dimensions of the changing flood insurance environment in New York City and explores the consequences for the city's residents and businesses.